OPTIMIZING EDUCATION STUDENTS’ PUBLIC SPEAKING SKILLS AS AN EFFORT TO IMPROVE TEACHER COMPETENCE - Simbolon, Santa Olivia Sharon (Universitas Negeri Medan, 2024)
This study aims to evaluate the improvement of future educators' public speaking skills through training focused on their final results. In the third meeting, there was a significant improvement of 71.32% in the students' public speaking skills after the post-test. This result showed a good improvement from the previous pre-test. Good public speaking skills are very important for future educators, as this will affect their competence in becoming professional teachers. The teacher's ability to explain the material briefly but comprehensively is needed so that students can understand well. This research makes an important contribution in preparing future educators to communicate effectively, avoid difficulties during the learning process, and improve their public speaking skills.